'Thank you for having me': The experiences and meanings of release from prison in Norway and England & Wales. Issue 2 (July 2022) - Doxat-Pratt, Sarah; Schliehe, Anna; Laursen, Julie
The day of release from prison can be one of the most highly anticipated events for prisoners, and one which holds a place in the public imagination as a significant and transformative moment. Yet in scholarly literature, although there is much on prisoner resettlement and reintegration, the moment of release itself is seldom mentioned. Drawing on interviews ( N :455) from a comparative research project in Norway and England & Wales, this paper will zoom in on the micro-processes that shape exit, capturing how prisoners prepare for release, the procedures and practices of the release day, and their first encounter with the outside world. In both countries, there was a juxtaposition of personal significance and institutional banality around exit, which contrast sharply with the highly ritualistic processes of sentencing and entry and which frequently led prisoners to reflect on the nature of their punishment and the meaning of their time in prison. By highlighting the details of release, the paper will explore these ideas, probing the boundaries that exist between the inside and outside worlds and connecting the experiences of exit with conceptual ideas of how punishment is experienced and how prisoners create meaning.